1997
DOI: 10.1111/j.1365-2621.1997.tb04440.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Spoilage Bacterial Load on Meat by Fluorescein Diacetate Hydrolysis or Resazurin Reduction

Abstract: Resazurin reduction time (RR), fluorescein diacetate hydrolysis (FDA), and aerobic plate count (APC) were monitored in aerobically packaged beef steaks stored at 4ЊC. FDA hydrolysis increased, while RR decreased with increased APC. As bacterial load increased from ca. 10 2 CFU/cm 2 to 10 8 CFU/cm 2 , FDA activity (A 490 ) increased from 0.1 to 0.6 units and RR decreased from 22 hr to Ͻ1 hr. Linear regression performed between APC and RR, and APC and FDA revealed r-values of 0.94 (PϽ 0.001) and 0.92 (PϽ 0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…To determine if activity levels were limiting organisms at low temperatures, we examined the metabolic activity of isolates via the reduction of resazurin (Venkitanarayanan et al ., 1997). The kinetics of resazurin reduction for four different isolates (2b, 3a, 5 and 8) at four different temperatures (22, 10.5, 4, − 10°C) were determined.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if activity levels were limiting organisms at low temperatures, we examined the metabolic activity of isolates via the reduction of resazurin (Venkitanarayanan et al ., 1997). The kinetics of resazurin reduction for four different isolates (2b, 3a, 5 and 8) at four different temperatures (22, 10.5, 4, − 10°C) were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one‐half of each steak was blended using a Handy‐Chopper™ (Black‐Decker, Shelton, Conn., U.S.A.). Total of 11 g of the blended tissue were transferred into individual sterile Whirlpak bags containing 99 mL of sterile Butterfields Phosphate buffer and pulsified, using a Pulsifier™ (Filtaflex Ltd., Almonte, Ontario, Canada) for 60 s. This was followed by standard dilutions and plating using the spread plate technique onto plate count agar and incubated at 25 °C for 48 h following accepted methods of sampling, preparation, and enumeration (Banwart 1989; FDA 1995; Venkitanarayanan and others 1997; Jay 2000). Mean values represented the 3 determinations.…”
Section: Methodsmentioning
confidence: 99%
“…The FDA hydrolysis value reached beyond the acceptable value for samples T3 and T6, T2 and T5, and T1 and T4 on day 3, 5 and 7 of refrigerated storage respectively which coincide with of spoilage in stored buffalo meat. Venkitanarayanan et al [8] reported a FDA hydrolysis in biceps femoris steaks under thawing and n=3, C=Control, T1=Treatment 1 (exposed at 25±1°C for 6 h), T2=Treatment 2 (exposed at 25±1°C for 12 h), T3=Treatment 3 (exposed at 25±1°C for 18 h), T4=Treatment 4 (exposed at 37±1°C for 4 h), T5=Treatment 5 (exposed at 37±1°C for 8 h), T6=Treatment 6 (exposed at 37±1°C for 12 h), ND=Not detected. *The spoiled meat sample was analyzed to study the extent of variation in parameters due to prolonged storage.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA hydrolysis of meat samples were measured according to the procedure described by Venkitanarayanan et al [8] with suitable modifications. One gram of meat was drawn from each sample, observing necessary aseptic precautions.…”
Section: Fda Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation